Penggunaan Model Tipe STAD dalam Materi Ajar Sistem Reproduksi di Sekolah Menengah - Ibrahim Ibrahim (Biotik, 2016)
The teacher ability to use instructional model is one of efforts to ease the teaching learning process. Teacher activity to use cooperative learning model with STAD type (students Achievement Division) engage students to participate actively in the classroom. Teacher acts as a facilitator to help students to achieve instructional goals in the concept of human reproductive system. Teachers need to use teaching strategies that facilitate students in following the teaching materials as well as get full information from various sources. Each teacher can manage the classroom as a solid team among students by selecting a heterogenous members of the group from different category such as low level, clever, very clever to work together and to enable them to participate actively in their group. Therefore the model of Cooperative Learning Team Achievement Division can help students and teachers to conduct an active teaching and learning process in the classroom. In the end, it is expected that a heterogenous cooperative group can result to a better learning outcomes in the concept of human reproductive system.